A Design for Evaluating Vocational Education Which Can Be Implemented within School Systems - Dangel, Timothy R.; Rhoades, Thomas W.; Anne Arundel County Public Schools, Annapolis, MD. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
This evaluation report describes the process by which a large, urban-suburban school system evaluated its vocational education program and the results of the evaluation. The evaluation was built upon a set of broad evaluation questions addressing two components of the vocational-technical program: (1) questions related to employer needs and program planning, and (2) questions related to the vocational-technical centers and the comprehensive high school programs. Although the specific program area of focus was vocational-technical education, the design is applicable to other curricula. The evaluation, which was advised by representatives of the public and local industry, provided for survey data from a variety of sources which impacted on or were impacted by vocational education. The value of the design is that it is manageable, can be implemented by a small staff, uses instruments which, although locally constructed, appear to be valid, and provides for a report of results which is comprehensive yet understandable by a lay board of education and which provides direction for ongoing program refinement and improvement. (Author/PN)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (67th, Montreal, Quebec, April 11-15, 1983). Paper copy not available due to marginal legibility.
Policymakers.
Community.
Parents.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Data Analysis; Evaluation Methods; Models; Program Evaluation; School Districts; Vocational Education; Anne Arundel County Public Schools MD; Speeches/Meeting Papers; Reports, Evaluative